Nilai Budaya dalam Penggunaan Bahasa Arab pada Aspek Sosial Masyarakat Indonesia: Studi Kualitatif Antropolinguistik: Penelitian - Annisa Putri Asis Lubis; Aulia Pramudita; Hazira Salsabila Arzli; Nursukma Suri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the role of Arabic in shaping the cultural values ​​and social identity of Indonesian society through a qualitative anthropolinguistic approach. Arabic, as the primary language of Islamic teachings, serves not only as a means of religious communication but also as a medium for transmitting cultural values ​​such as religiosity, politeness, solidarity, and morality. Data were obtained through observation, in-depth interviews with two informants (Buk Asmita, 48, and Nenek Murni, 65), and documentation of socio-religious activities. The results show that Arabic terms such as alhamdulillah, bismillah, and masya Allah have become integrated into daily social interactions as symbols of piety, respect, and prayer. Arabic plays an important role in strengthening social cohesion and maintaining the continuity of moral values ​​between generations. This study confirms that the use of Arabic reflects the integration of religion, culture, and the collective identity of the religious and polite Indonesian Muslim community.